The effect of the nisin-based pharmaceutical formulation used in the treatment plan for cows with subclinical mastitis on the milk microbiota - M. N. Isakova; Ya. Yu. Lysova (Ветеринария сегодня)
Due to the growing threat of antimicrobial resistance, the search and development of new drugs to treat infectious mammary gland diseases of high yielding cows is an urgent task. The paper presents data on the microbiota composition of milk from high yielding cows suffering from subclinical mastitis; 144 microbial isolates were recovered from 70 milk samples; with the highest number of Staphylococcus aureus and Streptococcus dysgalactiae detected (22.2 and 16.0%, respectively). The study showed that a significant number of Staphylococcus aureus isolates (53.1%) were resistant to I generation cephalosporins; 52.6% of the isolated Streptococcus dysgalactiae strains showed resistance to tetracyclines; 33.3% of Staphylococcus haemolyticus isolates were resistant to macrolides. 42.1; 35.3 and 62.5% of Enterococcus faecium, Aerococcus viridans and coliform bacteria isolates, respectively, were resistant to penicillins. 38.5% of Staphylococcus epidermidis isolates were found to be resistant to tetracyclines. Corynebacterium pseudotuberculosis isolates showed equal resistance to penicillin and tetracycline antimicrobials (20.0%). The research revealed presence of multi-drug resistant coliform bacteria, Streptococcus dysgalactiae, Aerococcus viridans, Staphylococcus aureus strains. Experiments to study the effect of the new nisin-based pharmaceutical formulation on microbiota of milk from cows with subclinical mastitis were carried out using 35 high yielding cows. A microbiological testing of cow milk on day 14 from the beginning of the treatment showed that the number of microbiota-free samples increased to 88.6%, while in 1.4% of cases Staphylococcus aureus isolates were recovered (103 CFU/mL). The titers of coliform and Staphylococcus aureus bacteria isolated in 1.4% (101 CFU/mL) and 2.7% (102 CFU/mL) of cases, respectively, were not etiologically significant.